Kinetics and Thermodynamics of Peppermint Oil Extraction from Peppermint Leaves - M. Kurji, Badoor; Abed, Khalid M.; A. Rashid, Sarmad; A. Abdulmajeed, Basma (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
This study aimed to extraction of essential oil from peppermint leaves by using hydro distillation methods. In the peppermint oil extraction with hydro distillation method is studied the effect of the extraction temperature to the yield of peppermint oil. Besides it also studied the kinetics during the extraction process. Then, 2nd -order mechanism was adopted in the model of hydro distillation for estimation many parameters such as the initial extraction rate, capacity of extraction and the constant rat of extraction with various temperature. The same model was also used to estimate the activation energy. The results showed a spontaneous process, since the  Gibbs free energy had a value negative sign.